KONSEP ALL YOU CAN EAT DITINJAU DARI SEGI HUKUM EKONOMI SYARIAH (STUDI DI WARUNG BAMBU, KEL. MANURUNGE, KAB. BONE) - ika, Triska tris; Jasmin, Suriah Pebriyani (IAIN BONE, 2024)
This thesis discusses the all you can eat concept from the perspective of sharia economic law. The aim of this research is to determine the practice of buying and selling food with the all you can eat concept at Warung Bambu, Kel. Manurunge, District. Bone and to find out the practice of buying and selling food with the all you can eat concept at Warung Bambu, Kel. Manurunge, District. Bone. This research is descriptive qualitative field research with a normative theological approach, a sociological approach and a muamalah fiqh approach. The research results show that, firstly, the practice of buying and selling food with the all you can eat concept at Warung Bambu, Kel. Manurunge, District. Bone is a concept that consumers can enjoy and eat as much food as they like, for just one payment. Of course, the food being bought and sold is 100% halal. The practice of buying and selling food with the all you can eat concept uses a direct contract with consent and acceptance from the seller and buyer. Second, a review of sharia economic law regarding the practice of buying and selling food with the all you can eat concept at Warung Bambu, Kel. Manurunge. Regency. Bone, in terms of the contract, terms and terms of sale and purchase, is said to have fulfilled the terms of sale and purchase. Keywords: All You Can Eat; Sharia Economic Law.